Ultrasound examination of the liver post mortem: are there any changes in size after autopsy? - I. A. Opryshko; V. A. Izranov; V. S. Gordova; M. S. Shushval; S. A. Stepanyan; Kh. Abdujabborov (Сибирский научный медицинский журнал, 2024)
The liver size is important to take into account when it is necessary to assess the course and severity of various diseases, including infectious, malignant and systemic diseases. The liver linear dimensions of the same patient depend on the method of examination (palpation, percussion, sonography, computed tomography, magnetic resonance imaging). The objective of this investigation was to compare the linear diameters of the liver according to ultrasound data of cadavers before autopsy and liver linear diameters after extraction of it from the abdominal cavity. Material and methods. All data were obtained in the pathology department of the Regional Clinical Hospital of the Kaliningrad Region. We examined 25 cadavers (12 females and 13 males). Before the autopsy we performed the ultrasound examination with measuring of the linear diameters of the functional left and right lobes with a convex transducer of a portable S6 ultrasound system (SonoScape, China). After the autopsy we did 3 sagitally oriented incisions for maximum linear measurements similar to previous ultrasound ones. Results and discussion. After extraction of the liver from the abdominal cavity the anteroposterior diameters of both lobes decreased on average by half after autopsy (p < 0.001), the craniocaudal diameters of the left and right lobes, on the contrary, increased on average 2 times and 1.25–1.35 times respectively (p < 0.001). The oblique craniocaudal maximum diameter of the right lobe increased (“stretches”) by an average of 1.11–1.15 times (p = 0.002). Conclusions. After extraction of the liver from the abdominal cavity all the linear diameters changed. The oblique craniocaudal maximum diameter of the right lobe is the most “stable”, due to which it possible to imagine the intravital diameter of the liver.